The 5S RNA genes of Schizosaccharomyces pombe. - Mao, J (1982)
The genomic arrangement and sequences of S. pombe 5S RNA genes are reported here. The 5S gene sequences appear to be dispersed within the genome, and are found independently of other rRNA genes. The sequences of two 5S genes examined show identical coding regions of 119 base pairs but have widely varying flanking sequences. A tRNAAsp gene is found in the 3' flanking region of one of the 5S genes. The tRNAAsp gene is faithfully transcribed in an X. laevis in vitro system, while the 5S genes are not transcribed in this system. The phylogenetic position of S. pombe is examined through comparison of 5S RNA sequences.